Ultrasound examinations in comparison with single X-ray absorptiometry in the diagnostics of osteoporosis - Bolanowski, Marek; Jędrzejuk, Diana; Pluskiewicz, Wojciech; Pruska, Dorota (Menopause Review/Przegląd Menopauzalny, 2006)
The aim of the study: Aim was to assess the utility of three different ultrasonic methods in osteoporosis diagnostics in comparison with single-energy X-ray absorptiometry (SXA) in group of women. Material and methods: Amplitude-dependent speed of sound (Ad-SoS) at hand phalanges was carried out using Sonic, ultrasonic parameters of the heel were studied by Achilles, and skin thickness was assessed by Osteoson in 38 women, the results were compared with results of forearm bone mineral content (BMC) and bone mineral density (BMD) studied by SXA using DTX-100 apparatus. Results: We have observed positive correlations between Ad–SoS by Sonic and: radius BMC (r=0.46; p=0.0374); radius BMD (r=0.65; p=0.0012); ulna BMC (r=0.,62; p=0,0026); ulna BMD (r=0.71; p=0.0003); distal forearm BMC (r=0.54; p=0.0122) and distal forearm BMD (r=0.68; p=0.0006). Similarly, positive correlations were shown in study by Achilles between stiffness index for young adults and ulna BMC (r =0.66; p=0.037) and ulna BMD (r=0.75; p=0.013), and between broadband ultrasound attenuation (BUA) and radius BMC (r=0.67; p=0.033) and ulna BMC (r=0.80; p=0.0053). Conclusions: 1. Quantitative ultrasound measurements of hand phalanges and heel are useful screening method for the assessment of bone quality. 2. Skin thickness studies by ultrasound reflect to lesser extent bone changes shown by other methods.